O ( D , D ) -covariant formulation of perfect and imperfect fluids in the double geometry - Lescano, Eric (2024)
We study generic matter coupled to a -dimensional supergravity using a formulation of double field theory (DFT), where all the fields are encoded in O⁡(,) multiplets. We study both the case when the matter comes from a variational principle, as well as the case where the matter comes from a statistical or thermodynamic approach. For the latter, we construct the distribution function for the perfect fluid and its entropy current, which is a conserved quantity. We then include general viscous and elastic terms in the generalized energy-momentum tensor which, in the general case, lead to entropy production. We consistently deform the conservation law of the generalized entropy current and identify a particular nondissipative deformation. Using the generalized fluid model, we revisit the issue of noncovariance of perfect fluids under T-dualities and we show how to resolve it in our DFT model with matter.